Rancang Bangun Prototipe Pembangkit Listrik Tenaga Mikrohidro Menggunakan Turbin Pelton - Chandra Bhuana; Tasrif Tasrif; Muhammad Ruswandi Djalal; Nurul Andini; Muhammad Aldy Rezaldy (Jurnal Teknik Mesin Sinergi, 2022)
Water energy can be used as a power plant by utilizing the available potential energy (waterfall potential and flow velocity). The water turbine is one of the driving machines where the working fluid is water which is used directly to rotate the turbine runner and turbine generator to produce electrical energy. This research was conducted using a Pelton type water turbine installation and measurements were made of turbine and generator rotation, flow rate, electric voltage and electric current with variations in the position of the nozzle angle. The research method used is a laboratory-scale experimental method and the results of the design of the water turbine are used as a practicum tool for students of the Department of Mechanical Engineering, Energy Generation Engineering Study Program. The results showed that there was an effect of the position of the nozzle angle on the performance of the PLTMH prototype using a Pelton turbine, in this study the nozzle position will be designed at an angle of 00,450,600, and 750.